Pengaruh Social Media Marketing, Kualitas Produk, Dan Online Customer Review Terhadap Keputusan Pembelian (Studi Kasus Pada Online Shop Syamilahhijab) - Nalurita, Iedilia Izza; Basalamah, Muhammad Ridwan; Wahyuningtyas, Nanik (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The development of e-commerce in Indonesia has driven changes in consumer behavior, including the purchase of hijab products through social media. Syamilahhijab, as one of the local brands, utilizes digital marketing strategies, product quality, and customer reviews as its main attractions. This study aims to analyze the influence of social media marketing, product quality, and online customer reviews on consumer purchasing decisions. The research approach used is quantitative with an explanatory research method. A total of 85 respondents were selected using purposive sampling, and data were collected through online questionnaires. Data analysis was carried out using multiple linear regression with SPSS version 25. The results show that simultaneously, all three independent variables have a significant influence on purchasing decisions. However, partially, only online customer reviews have a significant influence on purchasing decisions, while social media marketing and product quality do not show a significant effect. These findings indicate that customer reviews play a crucial role in shaping consumer perception and decision-making in the context of online shopping. This research provides practical implications for business actors to focus their strategies more on managing customer reviews in a positive and consistent manner. Keywords: Purchasing Decision, Social Media Marketing, Product Quality, Online Customer Review, E-Commerce.